Análise físico-química do MTA e do cimento Portland associado a quatro diferentes radiopacificadores - Costa, Bernardo César [UNESP]; Campos, Celso Neiva; Duarte, Marco Antono Hungaro; Chaves, Maria das Graças Afonso Miranda; Grizzo, Larissa Tercilia; Tanomaru Filho, Mario [UNESP] (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
INTRODUCTION: Mineral Trioxide Aggregate (MTA) is composed of Portland cement (PC), and a radiopacifier (bismuth oxide). OBJECTIVE: To evaluate the setting time, solubility, pH, calcium ion release and radiopacity of pure Portland cement and its association to four radiopacifiers, (Barium sulfate, bismuth carbonate, bismuth oxide and iodoform), and White MTA (Angelus, Londrina, Brazil). MATERIAL AND METHOD: The ratio CP/radiopacifier used was 4:1 by weight (80% Portland cement and 20% radiopacifier). The setting time was evaluated according the specification ADA 57. The solubility was analyzed according to ISO 6876/2001 specification. The pH was evaluated using a digital pHmeter and the release of Ca++ ions by atomic absorption spectrophotometer. The radiopacity was measured in millimeters of aluminum (mm/Al). The results were submitted to ANOVA and Tukey tests using 5% of significance level. RESULT: Barium sulfate did not alter the final setting time of the PC. Observed radiopacity was less than the minimum recommended by ADA 57 and ISO 6876/2001 for CP and CP associated with barium sulfate. The PC associated with iodoform showed solubility above the 3% recommended by ISO 6876/2001. All materials provided alkalinization and promoted calcium ion release. CONCLUSION: Bismuth carbonate and bismuth oxide provided proper initial setting time, solubility, pH, calcium ion release and radiopacity when combined with CP.

INTRODUÇÃO: O Mineral Trióxido Agregado (MTA) é composto por cimento Portland (CP) e um radiopacificador (óxido de bismuto). OBJETIVO: Avaliar tempo de presa, solubilidade, pH, liberação de íons Cálcio e radiopacidade do cimento Portland puro ou associado a quatro radiopacificadores (sulfato de bário, carbonato de bismuto, óxido de bismuto e iodofórmio), comparados ao MTA branco (Angelus, Londrina, Brasil). MATERIAL E MÉTODO: A proporção empregada CP/radiopacificador foi de 4:1 em peso, (80% de cimento Portland e 20% de radiopacificador). A especificação 57 da ADA foi usada para avaliação do tempo de presa. A solubilidade foi analisada segundo a especificação ISO 6876/2001. A avaliação do pH foi realizada com peagâmetro digital e a liberação de íons Ca++foi verificada por meio de espectrofotômetro de absorção atômica. A radiopacidade foi determinada em milímetros de alumínio (mm/Al). Os resultados foram submetidos aos testes de Análise de Variância e Tukey, nível de significância 5%. RESULTADO: O sulfato de bário não alterou o tempo de presa final do CP. Radiopacidade inferior ao mínimo recomendado pelas normas da ADA nº 57 e ISO 6876/2001 foi observada para CP e CP associado com sulfato de bário. O CP associado ao iodofórmio apresentou solubilidade acima dos 3% recomendados pela ISO 6876/2001. Todos os materiais proporcionaram alcalinização do meio e promoveram liberação de íons cálcio. CONCLUSÃO: Carbonato de bismuto ou óxido de bismuto proporcionaram tempo de presa inicial, solubilidade, pH, liberação de íons Cálcio e radiopacidade adequados quando associados ao CP.
Physicochemical analysis of MTA and Portland cement associated with four different radiopacifiers
Keywords: Mineral trioxide aggregate; Retrograde obturation; Root-end filling materials; Mineral trióxido agregado; Obturação retrógrada; Materiais retrobturadores